PLA2R and THSD7A: Disparate Paths to the Same Disease? - Beck, Laurence H. (J Am Soc Nephrol, 2017)
The phospholipase A2 receptor (PLA2R) and thrombospondin type-1 domain-containing 7A (THSD7A) are the two major autoantigens in primary membranous nephropathy (MN), and define two molecular subclasses of this disease. Both proteins are large transmembrane glycoproteins expressed by the podocyte, and both induce IgG4-predominant humoral immune responses that produce circulating autoantibodies that can be used clinically for diagnostic and monitoring purposes. The biologic roles of these proteins remain speculative, although several features of THSD7A suggest a role in adhesion. PLA2R-associated MN was initially found to associate with risk alleles within HLA-DQA1, but subsequent studies have shifted the focus to the HLA-DRB locus. Three distinct humoral epitope-containing regions have been defined within the extracellular portion of PLA2R, and it appears that the number of targeted epitopes may determine disease severity. Although similar information is not yet available for THSD7A-associated MN, this form of MN may have a unique association with malignancy. Finally, it appears likely that other autoantigens in primary MN exist. Although protocols similar to those that identified PLA2R and THSD7A may be successful in the identification of novel antigenic targets in MN, newer techniques such as laser-capture mass spectrometry or protein arrays may be helpful as well.